AI Mammography vs. Double Reading: A New Paradigm in Breast Cancer Screening - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of breast cancer screening is undergoing a profound transformation, driven by the integration of Artificial Intelligence AI. For decades, doubl...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning